2014
DOI: 10.2478/s13545-014-0115-1
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance of Staphylococcus-like organisms isolated from a recreational sea beach on the southern coast of the Baltic Sea as one of the consequences of anthropogenic pressure

Abstract: Antibiotic resistance of Staphylococcus-like organisms (STLO) isolated from a recreational sea beach located on the southern coast of the Baltic Sea was studied. The results of the present study showed that STLO inhabiting sand and seawater of the beach strongly differed in the resistance level to tested antibiotics. These microorganisms were most resistant to ampicillin, penicillin, oxytetracycline and susceptible to gentamicin, neomycin and streptomycin. Moreover, the level of antibiotic resistance among bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…The transmission of resistance (R-factor), a plasmid-mediated genetic determinant, may be credited with the development of MAR among these isolates [ 62 ]. Studies have shown an upward pattern in the incidences of S. aureus isolates with multiple antibiotic resistance [ 66 , 67 , 68 , 69 ]. It has also been reported that S. aureus isolates with multiple antibiotic resistance attributes have a negative impact on the treatment of staphylococcal infections, especially in elderly, children, and immune-compromised individuals [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transmission of resistance (R-factor), a plasmid-mediated genetic determinant, may be credited with the development of MAR among these isolates [ 62 ]. Studies have shown an upward pattern in the incidences of S. aureus isolates with multiple antibiotic resistance [ 66 , 67 , 68 , 69 ]. It has also been reported that S. aureus isolates with multiple antibiotic resistance attributes have a negative impact on the treatment of staphylococcal infections, especially in elderly, children, and immune-compromised individuals [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The marine environment is made up of a wide variety of bacteria; some of which are non-pathogenic and some, potentially pathogenic. 24 This study showed that some potentially pathogenic bacteria, some of which belong to the ESKAPE bacterial group of pathogens as well as the GLASS (Global Antimicrobial Resistance and Use Surveillance System) priority pathogens such as Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus spp. Acinetobacter are present in beach sand.…”
Section: Discussionmentioning
confidence: 98%
“…For humans, the main concerns are bioaccumulation in our food, resistance to antibiotics and the toxicity of pharmaceutical mixtures and their effect on the human organism (Skórczewski et al 2014;Fent et al 2006;Klatte et al 2016). Different studies show that the ecotoxic effect concentration of pharmaceutical mixtures are several times lower compared to pure active substances (Fent et al 2006).…”
Section: Risks For Organisms and Humansmentioning
confidence: 99%